Manajemen Paduan Suara Consolatio Universitas Sumatera Utara - Octaviana Tobing (Gondang: Jurnal Seni dan Budaya, 2018)
This study aims to determine the management of the University of North Sumatra Consolatio Choir, regarding planning, implementation, and monitoring of evaluations that have been carried out. This study uses a qualitative descriptive analysis approach. Data collection is obtained through: interviews, observation and documentation studies. The research informants were the Chair of the Daily Management Board, Conductor, and Members of the USU Consolation Choir. Data analysis was performed using qualitative data analysis and with technical inductive analysis. Qualitative research is basically building theory, so in this study there is a new theory that is built namely "Service Management". Service here means that organizational management does not expect profits, but the organization still exists. USU's Consolatio Choir, an informal organization, from the outset of planning, the organization has presented the organization's vision and mission to prospective members from USU students and alumni, which in its implementation, the organization's mission went well and everything that was done selflessly and feared God . After the evaluation monitoring, there were still a few weaknesses in non-technical management by BPH. Conclusion of research, choirs can be formed from USU students, or can even be formed from any group who wants to sing in a choir.